Vanadium-dependent haloperoxidase activity and phlorotannin incorporation into the cell wall during early embryogenesis of Fucus vesiculosus (Phaeophyceae). Issue 3 (2nd July 2020) - Lemesheva, Valeriya; Birkemeyer, Claudia; Garbary, David; Tarakhovskaya, Elena
ABSTRACT: Vanadium-dependent haloperoxidases (V-HPO) are specific enzymes involved in the metabolism of reactive oxygen species in marine algae. These enzymes contribute to early embryogenesis of algae in the order Fucales, catalyzing the reactions which result in phlorotannin incorporation into the newly forming zygote cell wall and adhesive material. In this study we showed that early embryogenesis in Fucus vesiculosus is accompanied by synchronous changes of V-HPO activity, hydrogen peroxide content and content of cell-wall-associated phlorotannins. Phlorotannin incorporation into the cell wall of Fucus zygotes had already begun 1 h after fertilization, and this process was accompanied by rapid increase of H2 O2 content and V-HPO activity. We suggest that altogether this initiates polymerization of phenolics and their cross-linking with the major cell wall constituent, alginic acid. Presumably, de novo phlorotannin biosynthesis is involved in this process, as GC-MS analysis showed dramatic changes in content of intracellular phloroglucinol and low-molecular-weight phlorotannins during the first 9 days of F. vesiculosus embryogenesis.